2007
DOI: 10.1002/bit.21732
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate models for prediction of rheological characteristics of filamentous fermentation broth from the size distribution

Abstract: The main purpose of this article is to demonstrate that principal component analysis (PCA) and partial least squares regression (PLSR) can be used to extract information from particle size distribution data and predict rheological properties. Samples from commercially relevant Aspergillus oryzae fermentations conducted in 550 L pilot scale tanks were characterized with respect to particle size distribution, biomass concentration, and rheological properties. The rheological properties were described using the H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2
2

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 27 publications
1
22
0
Order By: Relevance
“…Petersen et al [73] proposed, using principal components analysis, a prediction of apparent viscosity, yield stress and consistency index from the size distribution and biomass concentration. Based on Aspergillus orizae cultures, they assumed a constant power-law index around 0.4 and reported accurate correlations between predicted and experimental parameters (k and τ 0 ).…”
Section: Structure and Consistency Indexmentioning
confidence: 99%
“…Petersen et al [73] proposed, using principal components analysis, a prediction of apparent viscosity, yield stress and consistency index from the size distribution and biomass concentration. Based on Aspergillus orizae cultures, they assumed a constant power-law index around 0.4 and reported accurate correlations between predicted and experimental parameters (k and τ 0 ).…”
Section: Structure and Consistency Indexmentioning
confidence: 99%
“…Although biomass was high at 130 g/L dcw, broth consisted of loosely aggregated mucoid clumps of mycelia, suspended in a black liquid containing unicellular bodies suspected to be conidia. A few atypical cultivations attained similar biomass levels but possessed unexpected markedly lower viscosities below 300 cP, suggesting a strong influence of factors not currently measured such as particle size distribution [53]. Broth supernatant was Newtonian and not significantly different in viscosity than uninoculated medium; thus secreted extracellular polysaccharides [54] or other such compounds were not believed present.…”
Section: Scale-up Assessmentmentioning
confidence: 91%
“…Laser diffraction was introduced for the quantification of fungal morphology because of its rapid, unbiased and robust results for particle size distributions as manual sample preparation is eliminated [224]. However, this method fails to report any other descriptive factors such as the roughness or aspect ratio of the particles.…”
Section: Morphology Characterisationmentioning
confidence: 99%
“…It was found that laser diffraction resulted in similar particle size distributions to image analysis, whereas the standard deviations were generally higher, presumably because of discrepancies between the assumptions for the mathematical model and the biological sample and statistical artefacts based on the small number of particles analysed by image analysis. Studies on the application of laser diffraction for other filamentous organisms [55,198,224] as well as on other biological samples [226] indicate its applicability for the investigation of size distributions in process environments.…”
Section: Morphology Characterisationmentioning
confidence: 99%